Respuesta :
Answer:
[tex]x=\frac{-5+ln9}{3}[/tex] which appears to be from the list x=ln9-5/3
Step-by-step explanation:
We take the natural logarithm of both sides as the inverse operation to an exponent on e. This allows us to use log rules to rearrange the problem.
[tex]e^{3x+5}=9\\lne^{3x+5}=ln9 \\(3x+5)lne=ln9[/tex]
We know that as inverse operations, ln e =1.
[tex](3x+5)(1)=ln9\\3x+5=ln9\\3x=-5+ln9\\\frac{3x}{3}=\frac{-5+ln9}{3}[/tex]
[tex]x=\frac{-5+ln9}{3}[/tex]
Answer:
x = (ln (9)-5) /3
Step-by-step explanation:
e^3x+5=9
First we subtract 5 from each side
e^3x+5-5=9-5
e^3x=(9-5)
Then we take the natural log of each side
ln(e^3x) = ln(9-5)
3x = ln (9-5)
Then we divide by 3 on each side
3x/3 = ln (9-5) /3
x = ln (9-5) /3